EFEKTIVITAS PRENATAL YOGA TERHADAP PERNURUNAN NYERI PINGGANG PADA IBU HAMIL TRIMESTER III DI TPMB FITRI - Fathur Rohmah, Hajar Nur; Wulandari, Fitria; Anjani, Junih (Jurnal Delima Harapan, 2025)
Background: One of the discomforts that is often complained of by pregnant women is lower back pain. In some conditions it will improve on its own but more mothers still feel very uncomfortable with this complaint. In Indonesia, the prevalence of lower back pain in pregnancy is found to be 49% where 80-90% of mothers do not make any effort to overcome or reduce the complaint. One of the exercises that can be chosen for this complaint is prenatal yoga which has both physiological and psychological benefits in reducing lower back pain in pregnant women. Subjects and methods: The research design used was a quasi-experimental with one group pre-test - post-test design. The sample in this study was 30 pregnant women in the third trimester at TPMB Bidan F. The pain scale measurement used a numeric assessment scale. The statistical test used was the Wilcoxon test. Results: The results of the study showed a p value: 0.00 <0.05 which means there is a significant difference in the results of the lower back pain scale in the third trimester of pregnancy before and after doing prenatal yoga. Conclusion: Prenatal yoga has a positive and significant effect on reducing lower back pain in the third trimester of pregnancy at TPMB Bidan F in 2024.